"We're kind of at a pivotal point": Opt Out's vision for an ethic of care in a post-neoliberal era. Issue 1 (January 2020) - Schroeder, Stephanie; Currin, Elizabeth; McCardle, Todd
This article explores the Opt Out Florida (OOF) movement, a predominantly woman-led group seeking to dismantle neoliberal education policy by coaching children to boycott high-stakes standardized tests. Guided by Campbell's assertion that neoliberalism will never disappear without a "gender revolution" and Noddings's belief that those who have claimed power in the "traditional masculine structure" of our educational institutions will not readily cede their authority, we assert that movements like Opt Out are not only necessary to bring about a post-neoliberal future, but offer important insight into the role activist mothers may play in fulfilling that vision for all children. As a noticeably maternal movement, Opt Out displays a commitment to Noddings's description of moral education and her assertion that "if an enterprise precludes…meeting the other in a caring relation, [one] must refuse to participate in that enterprise." Understanding standardized tests as instruments of control meant to defund and privatize public education, Opt Out members actively resist them. Their ethic of care eschews corporate influence, and guides both their mission to return control of the classroom to the local level and their rejection of the deskilling and intensification of the teaching profession. Drawing on critical ethnographic data from OOF, we ultimately argue that the movement's emphasis on the ideal moral and caring relations between school and child offers one example of what post-neoliberal education might look and sound like from a distinctly feminine perspective.